2017
DOI: 10.1111/jai.13247
|View full text |Cite
|
Sign up to set email alerts
|

Age and growth comparisons of Hovsgol grayling (Thymallus nigrescensDorogostaisky, 1923), Baikal grayling (T. baicalensisDybowski, 1874), and lenok (Brachymystax lenokPallas, 1773) in lentic and lotic habitats of Northern Mongolia

Abstract: Despite concern over the conservation status of many Mongolian salmonids and the importance of their ecological role in Mongolia's aquatic ecosystems, little is known about their basic biology. Hovsgol grayling (Thymallus nigrescens) is endemic to Lake Hovsgol, Mongolia and listed as endangered on the Mongolian Red List. Baikal grayling (T. baicalensis) and lenok (Brachymystax lenok) are found in lakes and rivers throughout the Selenge drainage. A detailed study of the age and growth of these three salmonids w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…This unique B. lenok phylogroup is genetically distinct and thus highly valuable in the context of genetic conservation for the species. Incidentally, this group has also been the focus of increased scientific research on B. lenok including studies on their feeding ecology (Olson, Jensen, & Hrabik, ), thermal tolerances (Hartman & Jensen, ), lotic and lentic growth comparisons (Tsogtsaikhan et al, ), and seasonal movements (Kaus, Büttner, Karthe, Schäffer, & Borchardt, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This unique B. lenok phylogroup is genetically distinct and thus highly valuable in the context of genetic conservation for the species. Incidentally, this group has also been the focus of increased scientific research on B. lenok including studies on their feeding ecology (Olson, Jensen, & Hrabik, ), thermal tolerances (Hartman & Jensen, ), lotic and lentic growth comparisons (Tsogtsaikhan et al, ), and seasonal movements (Kaus, Büttner, Karthe, Schäffer, & Borchardt, ).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of genetic distinction detected by the mtDNA marker analysis suggests there is either a significant amount of contemporary gene flow between Lake Hovsgol and Selenge basin inhabitants via the Eg‐Uur River or else it has ceased only recently. The morphological differences displayed by individuals that inhabit Lake Hovsgol, including significant differences in the length–weight and age–length relationships compared to T. baicalensis sampled from riverine environments (Tsogtsaikhan et al, ), are likely due to the high ecological flexibility and phenotypic plasticity of this genus, which has previously caused confusion between intraspecific forms in Lake Baikal (i.e., black and white Baikal graylings, Knizhin et al, ). However, the contrib analysis and the pairwise F ST values still indicated that individuals sampled from Lake Hovsgol, while not a separate species, displayed genetic differentiation from each other, which justifies the Lake Hovsgol population as a priority within the T. baicalensis ESU.…”
Section: Discussionmentioning
confidence: 99%
“…Saggital otoliths were collected opportunistically from 21 Hovsgol grayling and aged following the methods of Tsogtsaikhan et al (2017). Thin transverse sections of otoliths were examined under a compound microscope (50× magnification) using transmitted light, and age determination was made by one experienced reader.…”
Section: Otolith Age Analysismentioning
confidence: 99%
“…This salmonid inhabits the rivers and lakes of Siberia and northern Asia, including Mongolia, where it has been listed on the country's Red List of Fishes as vulnerable due to widespread population declines that have resulted from increased water pollution, habitat destruction, climate change and fishing activities (Dulmaa, 1999;Kottelat, 2006;Ocock et al, 2006). While fish capture and consumption have traditionally not been a major part of the local culture in Mongolia, this is changing rapidly (Chandra, Gilroy, Purevdorj, & Erdenebat, 2005;Bailey, 2012;Hogan & Jensen, 2013;Tsogtsaikhan et al, 2017) and thus the current widespread unregulated and illegal fishing operations that occur throughout the country has now been considered as the primary driver of B. lenok population declines. In response, authorities now need to adapt more comprehensive protection measures and improve management strategies to conserve and maintain robust B. lenok stocks in Mongolia.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on B. lenok has focused on phylogenetic origins of conspecifics (Froufe, Alekseyev, Alexandrino, & Weiss, 2008;Froufe, Alekseyev, Knizhin, Alexandrino, & Weiss, 2003;Shed'ko et al, 1996), spawning behaviour (Esteve & McLennan, 2008), feeding and diet (Chandra et al, 2005), thermal ecology (Hartman & Jensen, 2017) and biometric comparisons between lotic and lentic populations (Tsogtsaikhan et al, 2017). However, a detailed knowledge of this species' spatial ecology remains largely unknown, with only a single study being conducted on the re-described Brachymystax tsinlingensis Li 1966 (Xing et al, 2015) reported as B. lenok tsinlingensis in the Nakdong River, South Korea.…”
mentioning
confidence: 99%